Contribution of Manufacturing Strategy to Competitive Performance of Manufacturing Companies: Empirical Evidence from Vietnam - HoangMr., Hoa; Phan, Anh Chi; Le Thai, Phong (Organizations and Markets in Emerging Economies, 2020)
This paper presents the results of an empirical study examining the relationship between manufacturing strategy and competitive performance of Vietnamese manufacturers, with focus on the technology factor of manufacturing strategy. Statistical techniques were used to analyze the data collected from 25 manufacturing enterprises, and the qualitative research method was employed to enrich the captured results. Findings indicate the positive impact that manufacturing strategy (together with its components namely competitive priorities and technology choices) has on firm’s competitive performance. Two case studies also provided more in-depth knowledge of the development and implementation of manufacturing strategy at Vietnamese manufacturers. From there, recommendations are proposed for management to better implement manufacturing strategy and utilize technology in order to improve competitive performance.